Defining the optimal blanking period duration after cryoballoon pulmonary vein isolation in patients with atrial fibrillation who have never been treated with an antiarrhythmic drug. (14th October 2021) - Milstein, N; Saberito, M; Bhatt, A; Habibi, M; Sichrovsky, T; Preminger, M; Shaw, R; Mittal, S; Musat, D
Abstract: Background: Cryoballoon (CB) pulmonary vein isolation (PVI) is an approved method for ablation in patients with paroxysmal (PAF) or persistent (PeAF) atrial fibrillation (AF). Although the first 90 days post-ablation are considered within the blanking period (BP), the optimal duration of the BP remains undefined. Purpose: To objectively define the BP duration in pts undergoing CB PVI by evaluating a cohort never treated with an antiarrhythmic drug (AAD). Methods: We enrolled consecutive pts with either PAF or PeAF who underwent initial CB PVI; all pts had an implantable loop recorder (ILR) for long-term ECG monitoring. No pt received an AAD either before or after ablation. We determined the time to last AF episode within the first 90 days of ablation. We then correlated this to the likelihood a patient had recurrent AF between 91 and 365 days of ablation. Results: There were 45 pts (67±8 years; 26 [58%] male; 40 [89%] PAF; CHA2DS2-VASc 2.6±1.3). We defined 4 distinct groups post ablation based on whether or not they had AF in the BP: (1) no AF days 0–90 (n=19 [42%]), (2) last AF days 0–30 (n=11 [24%]), (3) last AF days 31–60 (n=3 [7%]), and (4) last AF days 61–90 (n=12 [27%]). After the 90-day BP, 15 (33%) pts had AF recurrence. Pts with no AF and those with AF only within 30 days of ablation had similar long-term outcome; however, recurrent AF more than 32 days after ablation predicted long-term ablation failure (Figure). Conclusion: The post CB PVI blanking period is just a month. AF recurrences beyond a month in patients not on an AAD are associated with AF recurrence in the majority of pts. Funding Acknowledgement: Type of funding sources: None.